Survey and Excavations in Central Oman, 1974-75 - de Cardi, B. (The Journal of Oman Studies, 1975)
In November, 1974, a small British Expedition visited Oman to carry out archaeological survey and excavation, a project made possible by a Fellowship from the Winston Churchill Memorial Trust and grants from the British Academy and the Society of Antiquaries of London. In Oman generous support was given by the Ministry ofinformation and Culture whose representatives, Mr. Ahmed Saif and Mr. Hamed Rashid, accompanied us in the field, and much assistance was afforded by the Sultan's Armed Forces and Petroleum Development (Oman), Ltd.